(untitled) (Journal of Fatima Jinnah Medical University, 2020)
Background: Retinopathy of prematurity (ROP) is a serious but preventable morbidity, leading to childhood blindness. The aim of this study was to analyze the incidence and risk factors of ROP in preterm babies. Subjects and methods: A prospective cohort study was conducted at Neonatology Unit, Hameed Latif Hospital, Lahore, from July 2017 to February 2019. All preterm babies born at Hameed Latif Hospital at ≤ 34 weeks of gestation, birth weight of <1.5 kg, born at 34-37 weeks of gestation with birth weight of 1.5- 2.5 kg having a significant course of illness, were included in the study. Their maternal history was obtained for gestational age, and maternal risk factors. Neonates were monitored and evaluated for clinical course, morbidity and mortality, during their stay at the hospital. These preterm neonates were screened for ROP by ophthalmological examination at 4-5 weeks of age. Data was analyzed to see the incidence of ROP and univariate and logistic regression analyses were applied to determine association of risk factors with ROP. Results: Twenty eight percent (n=21) of the total screened (n=75) preterm neonates, had developed ROP. Logistic regression analysis showed that anemia (with Hb<10g/dl or HCT <30%) (p=0.011), fraction of inspired oxygen (FiO2>40% (p=0.018) and birth weight<1.5 kg (p=0.048) were the risk factors associated with development of ROP. Conclusion: Development of protocols and their implementation in neonatal units to save newborns from the identified associated risk factors can help prevent development of ROP leading to childhood blindness.